Enhanced Optical Properties of Colored Semitransparent Ultrathin Hybrid Solar Cells Employing Fabry–Pérot Etalon With a Dielectric Overlay - Kyu-Tae Lee; Hyoung Won Baac; Dong Hyuk Park; Jong G. Ok; Hui Joon Park (IEEE Photonics Journal, 2018)
We investigate the effect of a dielectric overlay in a planar microcavity on optical performances of colorful, see-through ultrathin amorphous silicon/organic hybrid solar cells, where a conventional Fabry–Pérot cavity is integrated with a cathode. The proposed colored solar cell devices show an enhanced transmission efficiency by optimizing both a thickness and a refractive index of the dielectric overlay at a resonance wavelength, which is primarily attributed to a better admittance matching. In addition, a purity of semitransparent red, green, and blue colors is improved by increasing a thickness of metallic layers in the microcavity with little sacrificing the transmission efficiency; thus, achieving a wide color gamut coverage as compared to conventional liquid crystal displays. Furthermore, mitigating reflection losses at complementary wavelength ranges and creating sharp resonances lead to an improved photocurrent generation from the semitransparent hybrid solar cells. The study described in this work provides insights and possibilities to enhance the characteristic performances of diverse applications, such as energy-efficient display technologies and decorative solar cells.